2003
DOI: 10.1016/s0042-6822(03)00104-1
|View full text |Cite
|
Sign up to set email alerts
|

Localization of influenza virus proteins to nuclear dot 10 structures in influenza virus-infected cells

Abstract: We studied influenza virus M1 protein by generating HeLa and MDCK cell lines that express M1 genetically fused to green fluorescent protein (GFP). GFP-M1 was incorporated into virions produced by influenza virus infected MDCK cells expressing the fusion protein indicating that the fusion protein is at least partially functional. Following infection of either HeLa or MDCK cells with influenza A virus (but not influenza B virus), GFP-M1 redistributes from its cytosolic/nuclear location and accumulates in nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 70 publications
1
24
2
Order By: Relevance
“…The cellular localization of NS1 observed in our analyses appeared to be preferentially cytoplasmic, in contrast with previous studies that have shown a preferentially nuclear localization for NS1 (60)(61)(62)(63). Nevertheless, we observed the same cellular distribution of NS1 in cells expressing the non-SUMOylatable form of NS1 as well as in cells coexpressing the ASL, therefore conclusively indicating that dramatic changes in the percentage of SUMOylated NS1 in the cell do not translate into changes in its cellular distribution.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…The cellular localization of NS1 observed in our analyses appeared to be preferentially cytoplasmic, in contrast with previous studies that have shown a preferentially nuclear localization for NS1 (60)(61)(62)(63). Nevertheless, we observed the same cellular distribution of NS1 in cells expressing the non-SUMOylatable form of NS1 as well as in cells coexpressing the ASL, therefore conclusively indicating that dramatic changes in the percentage of SUMOylated NS1 in the cell do not translate into changes in its cellular distribution.…”
Section: Discussioncontrasting
confidence: 91%
“…Different intracellular localization patterns, including nucleolar, nuclear, at promyelocytic leukemia nuclear bodies (PMLNBs), and cytoplasmic, have been assigned to NS1 (60)(61)(62)(63), thus leading to the idea that NS1's cellular localization might be dependent on numerous factors, including the possible involvement of cellular factors (19). Since SUMOylation is known to affect the cellular localization of numerous SUMO targets, including that of several viral proteins (64-67), we decided to assess whether SUMOylation could be one of the cellular factors affecting NS1's cellular localization.…”
Section: Ns1 Sumoylation Affects Viral Growth In Ifn-competent and Ifmentioning
confidence: 99%
“…The orthomyxovirus influenza A virus-encoded matrix 1 protein (M1) has also been reported to be coupled with ND10 during infection with unknown consequences (51,52). M1 is the most abundant viral protein both in the virion (ϳ3000 molecules/ virion) and in the cell during infection.…”
Section: During Infection Viral Proteins Target Cellular Pathways Thmentioning
confidence: 99%
“…1B). M1 protein has been shown to associate with PML nuclear body proteins (51,52), and Daxx has been shown to repress RelB (38,39). Thus, during early infection of influenza A (2-8 h.p.i.…”
Section: Involvement Of M1 In Transcription Regulation Of Antiapop-mentioning
confidence: 99%
“…The results showing that Fyn-GFP fusion proteins efficiently transport to the plasma membrane but fail to produce any detectable GFP particles also support the statement of M1 having an inherent budding ability. Our observation that M1, in the absence of other viral proteins, was primarily targeted to the nucleus/perinuclear region initially came as a surprise but seems logical since M1 contains a well-documented nuclear signal, as demonstrated by several previous studies involving different approaches (1,51,57,67). It should be noted that our documented findings on M1 localization differ substantially from those reported previously using the M1-expressing vaccinia virus system (10,25,67).…”
Section: Discussioncontrasting
confidence: 43%